(untitled) (Bangladesh Journal of Anatomy, 2014)
Context: The importance of the knowledge of Cell and Histology in grasping the paraclinical and clinical sciences by medical undergraduates is understandable. The rapidly changing scenario of the concepts of teaching-learning and assessment demands assessing the status of undergraduates residual knowledge from the viewpoint of teachers, curriculum planners and educational researchers. Materials and methods: Answering text-based (60%) and illustration-based (40%) single-sentence True/ False questions was attempted by 373 undergraduates who had completed the Cell and Histology portion of their course 3 to 6 months earlier in two government and two private medical colleges of Bangladesh. There were structurally-oriented (46.67%), functionally-oriented (43.33%) and clinically-oriented (10%) questions addressing mainly recall (58%) and understanding (40.67%) levels of cognitive domain. Comparisons were made among the numbers of correct answers to different types of question using ANOVA Post Hoc and t test, as applicable. Results: The mean frequency of correct response was 54.25%. Significantly more (p= 0.00) correct responses were recorded for the clinically-oriented (62.47%) and functionally-oriented (54.46%) questions than for the structurally-oriented (52.62%) questions. There were significantly (p= 0.00) fewer correct responses for the understanding-level questions (51.13%) than for the recall-level questions (56.65%). Conclusion: These results suggest that the residual knowledge of Cell and Histology in the undergraduates, though not very rich, may be governed both by a sense of relevance and by memorisation. Further study with a larger sample can add to these results to dictate curriculum modification and implementation, regarding teaching and assessment, in making learning more relevant and less memorisation-dependent. DOI: http://dx.doi.org/10.3329/bja.v11i1.20507 Bangladesh Journal of Anatomy, January 2013, Vol. 11 No. 1 pp 34-43